2007
DOI: 10.1002/cphc.200700268
|View full text |Cite
|
Sign up to set email alerts
|

Single DNA Molecule Isolation and Trapping in a Microfluidic Device

Abstract: This paper presents a systematic method to isolate and trap long single DNA segments between integrated electrodes in a microfluidic environment. Double stranded lambda-DNA molecules are introduced in a microchip and are isolated by electrophoretic force through microfluidic channels. Downstream, each individual molecule is extended and oriented by ac dielectrophoresis (900 kHz, 1 MV m(-1)) and anchored between aluminium electrodes. With a proper design, a long DNA segment (up to 10 microm) can be instantly ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Electrophoretic and DEP forces were combined to improve separation by Kumemura et al and Regtmeier et al [119,125]. In the method by Kumemura et al, individual double-stranded DNA migrated through the device via electrophoretic force but was captured using DEP [119].…”
Section: Analysis Of Dnamentioning
confidence: 98%
See 1 more Smart Citation
“…Electrophoretic and DEP forces were combined to improve separation by Kumemura et al and Regtmeier et al [119,125]. In the method by Kumemura et al, individual double-stranded DNA migrated through the device via electrophoretic force but was captured using DEP [119].…”
Section: Analysis Of Dnamentioning
confidence: 98%
“…In the method by Kumemura et al, individual double-stranded DNA migrated through the device via electrophoretic force but was captured using DEP [119]. The device captured a single, long strand (10 mm) 48.5 kbp l-DNA.…”
Section: Analysis Of Dnamentioning
confidence: 99%
“…Cohen et al developed an anti-Brownian electrokinetic trap [56], in which a time-dependent electric field was applied to induce the electrokinetic drift to cancel the random diffusion of single molecules in aqueous solution. Kumemura et al reported another trapping device using AC dielectrophoresis [57], in which individual DNA molecules were extended and oriented in the electric field and anchored between the aluminum electrodes for long-term studies. The fluid fieldinduced single-molecule trapping at the intersection of microfluidic channels was reported recently [58].…”
Section: Smd In Integrated Microfluidic Devicesmentioning
confidence: 99%
“…Over the past several decades, the separation and concentration of biomolecules including DNA and proteins have been developed for micro-scale assay such as genetics, disease diagnostics and point-of-care applications [1]. Recently, novel biomolecules separation and detection methods based on ion concentration polarization (ICP) phenomena have been extensively developed [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…All authors read and approved the final manuscript. 1 Department of Electrical and Computer Engineering, Seoul National University, Seoul 08826, Republic of Korea.…”
mentioning
confidence: 99%